Application of international convention on human rights in British Coronial System as an example for Malaysia - Noorfajri Ismail (Fakulti Undang - Undang, 2010)
Coroner’s inquest or deaths investigation have always been regarded as a domestic law of the respective country. Therefore the local procedural legal framework on death enquiry is considered as a primary source of law. However investigation relating to who, how, where and on what manner the deceased came into his death are crucial issues pertaining to ‘right to life’ which is a salient feature of human right, a right that is internationally recognized via international convention. By virtue of Article 2 of European Convention on Human Rights (ECHR), everyone’s right to life shall be protected by law. This obligation vested upon the State to protect the right to life so as to form an effective official investigation whenever there are cases of individual unlawful killed or died as a result of the use of force by, inter alia agents of the State. Any deprivation of life must be subjected to the most careful scrutiny. For example inquiry into deaths in custody e.g. under the control of police or prison officers, the State is under an obligation to provide plausible explanation as to the cause of death. The issue is whether ECHR can be regarded as universal standard hence being referred to and applied for the local coroners in holding inquest proceeding particularly in investigating to death cases beyond term of reference provided by domestic law. Thus broadening the scope of coroner’s enquiry and compatible with the Convention right under Article 2. This paper will discuss the application of ECHR in UK coronial legal system by analyzing latest reported cases and the possibilities of Malaysian coroner to adopt the principle enunciated by the Convention in making the death investigation more effective